Open reduction and internal fixation with plating is beneficial in the early recovery stage for displaced midshaft clavicular fractures in patients aged 30–65 years old - Chu, Jian-Yuan (Tzu Chi Med J, 2018)
OBJECTIVES: Midshaft clavicular fractures are increasingly treated operatively rather than nonoperatively. Studies have shown mixed results for both types of treatment. The aim of this study was to compare the early-stage functional status associated with open reduction and internal fixation (ORIF) with plating and that associated with conservative treatment for displaced midshaft clavicular fractures. MATERIALS AND METHODS: A single-center retrospective review of the results of 120 cases of displaced midshaft clavicular fractures in patients aged 30–65 years old was conducted. The primary outcome was fracture union status at 6 months. Other outcomes were subjective shoulder value (SSV) scores, visual analog scale (VAS) scores, and radiographic shortening at 6 weeks, 3 months, and 6 months. The complication rates in the operative and nonoperative groups were recorded. RESULTS: The delayed union rate at 6-month postoperatively and VAS scores at 6 weeks, 3 months, and 6 months postinjury were significantly higher in the conservative treatment group than in the ORIF group. SSV scores were significantly improved at 6-month postinjury in the ORIF group. CONCLUSIONS: This is the first study to discuss the importance of early-stage functional restoration after ORIF with plating for displaced midshaft clavicular fractures. This surgery leads to lower pain complications in the earlier stages of bone healing and lower delayed union rates compared with conservative treatment, in patients aged 30–65 years old.